2002
DOI: 10.1159/000063241
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse in Kuwait: Problems in Management

Abstract: Objectives: To explore the extent of child abuse in Kuwait and examine the difficulties associated with its management. Subjects and Methods: A retrospective analysis of the 60,640 medical records of children admitted to Al-Amiri and Mubarak Al-Kabeer Hospitals, Kuwait, between 1991 and 1998 was done. Results: Of the 60,640 records, 16 children showed evidence of abuse. Of these, the perpetrator was a parent in 75% of the cases, which involved the following abuses: physical, 13; sexual, 2; and Munchausen syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…Most of the injuries occurred in the summer and autumn and in the evening, as opposed to during the day. Our assault rate was somewhat lower than that in the literature, probably due to underreporting of child abuse [21].…”
Section: Discussioncontrasting
confidence: 90%
“…Most of the injuries occurred in the summer and autumn and in the evening, as opposed to during the day. Our assault rate was somewhat lower than that in the literature, probably due to underreporting of child abuse [21].…”
Section: Discussioncontrasting
confidence: 90%
“…In Arab countries, child maltreatment in the home is widespread, yet underreported (Khamis 2000; Al‐Ateeqi et al . 2002; Thabet et al .…”
Section: Introductionmentioning
confidence: 99%
“…In Arab countries, child maltreatment in the home is widespread, yet underreported (Khamis 2000;Al-Ateeqi et al 2002;Thabet et al 2004;Al-Mahroos et al 2005;Al Eissa & Almuneef 2010). Haj-Yahia and Abdo-Kaloti (2003) found that Palestinian parents' frequent use of harsh corporal punishment led to children's physical injury.…”
Section: Introductionmentioning
confidence: 99%
“…Perpetrators being mainly non-parents was unexpected. Studies in Kuwait have conflicting findings regarding perpetrators (6,24). In contrast, physical abuse in the USA was mostly perpetrated by parents and sexual abuse by others (25,26).…”
Section: Perpetratorsmentioning
confidence: 99%